Article Review: Potential of Alkaloid Compounds from East Kalimantan Mangrove Plants as Antibacterial Agents - Aini, Kharis Matul; Astuti, Indah; Syahirah, Alya; Muhfidah Lutfia Ulfa; Usman; Wila (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Alkaloids are organic compounds characterized by a ring structure containing one or more nitrogen atoms and produced through secondary metabolism in plants and animals. Mangroves are woody plants that grow in wet, muddy, and brackish environments and are widespread in East Kalimantan. Some mangrove species found in this region include Avicennia sp., Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, Rhizophora stylosa Griff., Avicennia marina, and Bruguiera gymnorrhiza. This study uses a secondary research approach with a narrative review method to provide an overview and scientific information regarding mangrove leaf extract fractions from East Kalimantan that exhibit antibacterial activity. Data were collected from 60 scientific journals published between 2015 and 2025, sourced from electronic databases such as Google Scholar and Semantic Scholar. The review results indicate that mangroves in East Kalimantan possess high biodiversity and significant chemical potential, primarily due to their rich content of secondary metabolites, including alkaloids, flavonoids, tannins, terpenoids, and saponins, which contribute to various biological activities, including antibacterial, antioxidant, anti-inflammatory, and anticancer effects. The findings indicate that mangroves in East Kalimantan contain various secondary metabolites, particularly alkaloids, which contribute significantly to antibacterial activity. Among the species reviewed, Avicennia sp. and Avicennia marina exhibited the most consistent and potent antibacterial effects against several pathogenic bacteria. Overall, this review confirms that mangroves from East Kalimantan are a promising natural source for alkaloid-based antibacterial agents and have potential for further development in pharmaceutical applications.